2011
DOI: 10.1016/j.brainres.2010.10.095
|View full text |Cite
|
Sign up to set email alerts
|

Neuroanatomical changes due to hearing loss and chronic tinnitus: A combined VBM and DTI study

Abstract: Subjective tinnitus is the perception of sound in the absence of an external source. Tinnitus is often accompanied by hearing loss but not everyone with hearing loss experiences tinnitus. We examined neuroanatomical alterations associated with hearing loss and tinnitus in three groups of subjects: those with hearing loss with tinnitus, those with hearing loss without tinnitus and normal hearing controls without tinnitus. To examine changes in gray matter we used structural MRI scans and voxel-based morphometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

39
270
1
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 257 publications
(314 citation statements)
references
References 60 publications
39
270
1
4
Order By: Relevance
“…Naturally, a neuroanatomical examination that considers only gray matter traits is not complete. We agree that changes in white matter architecture can also be conceived as neuroplastic biomarkers of the tinnitus network [26,83,28]. As outlined by Adjamian and co-authors [33] these studies report both local increases and decreases of white matter fiber tracts in TI.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 52%
See 4 more Smart Citations
“…Naturally, a neuroanatomical examination that considers only gray matter traits is not complete. We agree that changes in white matter architecture can also be conceived as neuroplastic biomarkers of the tinnitus network [26,83,28]. As outlined by Adjamian and co-authors [33] these studies report both local increases and decreases of white matter fiber tracts in TI.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 52%
“…Accordingly, [66, p. 1141] concluded that "GM volume, which is a composite of 2 other traits (surface area and thickness), might not be the best choice". Even though recent clinical studies [27,28,31,13,35] continue to use VBM to identify apparent tinnitus-related group differences, we suggest that surface-based morphometry should be used in complement with VBM because it allows for the computation of three distinct parameters, namely CV, CSA, and CT. Thus, SBM minimizes the risk of underestimating or ignoring existing relationships between CT or CSA and behavior.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations